Lower Levels of GABAergic Function Markers in Corticotropin-Releasing Hormone-Expressing Neurons in the sgACC of Human Subjects With Depression - Oh, Hyunjung; Newton, Dwight; Lewis, David; Sibille, Etienne (Frontiers in Psychiatry, 2022)
Rationale A previous transcriptome meta-analysis revealed significantly lower levels of corticotropin-releasing hormone (CRH) mRNA in corticolimbic brain regions in major depressive disorder (MDD) subjects, suggesting that cortical CRH-expressing (CRH+) cells are affected in MDD. Rodent studies show that cortical CRH is mostly expressed in GABAergic interneurons; however, the characteristic features of CRH+ cells in human brain cortex and their association with MDD are largely unknown. Methods Subgenual anterior cingulate cortex (sgACC) of human subjects without brain disorders were labeled using fluorescent in situ hybridization (FISH) for CRH and markers of excitatory (SLC17A7), inhibitory (GAD1) neurons, as well as markers of other interneuron subpopulations (PVALB, SST, VIP). MDD-associated changes in CRH+ cell density and cellular CRH expression (n = 6/group) were analyzed. RNA-sequencing was performed on sgACC CRH+ interneurons from comparison and MDD subjects (n = 6/group), and analyzed for group differences. The effect of reduced BDNF on CRH expression was tested in mice with blocked TrkB function. Results About 80% of CRH+ cells were GABAergic and 17.5% were glutamatergic. CRH+ GABAergic interneurons co-expressed VIP (52%), SST (7%), or PVALB (7%). MDD subjects displayed lower CRH mRNA levels in GABAergic interneurons relative to comparison subjects without changes in cell density. CRH+ interneurons show transcriptomic profile suggesting lower excitability and less GABA release and reuptake. Further analyses suggested that these molecular changes are not mediated by altered glucocorticoid feedback and potentially occur downstream for a common modulator of neurotrophic function. Summary CRH+ cells in human sgACC are a heterogeneous population of GABAergic interneurons, although largely co-expressing VIP. Our data suggest that MDD is associated with reduced markers of inhibitory function in sgACC CRH+ interneurons, and provide further evidence for impaired GABAergic function in the cortex in MDD.